THE TEACHER AS SUBJECT OF THE PEDAGOGICAL PROCESS - Jumabayeva Mahzunabonu; Jalolova Muqaddas (TADQIQOTLAR, 2025)
The article examines the multifaceted role of the teacher as the primary subject of the pedagogical process. Emphasizing the teacher’s functions beyond the mere transmission of knowledge, the study highlights their active involvement in organizing, managing, and facilitating the educational environment. The teacher’s professional responsibilities are analyzed through didactic, educational, organizational, and communicative perspectives, reflecting the complexity of modern teaching practices. Special attention is given to the influence of the teacher’s personality on students’ motivation, emotional well-being, and academic achievements. The article underscores the importance of continuous professional development, reflective practice, and the acquisition of socio-psychological competencies. In conclusion, the study reaffirms the teacher’s central role in ensuring the effectiveness of the pedagogical process and fostering the holistic development of learners.